A qualitative analysis to determine the critical features of a frontside bottom turn in professional surfing - Whitting, J. W.; Brinsmead, R.; Forsyth, J. R.; Hollier, J.; Crowley-McHattan, Z. J. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Surfing bottom turns underpin the quality of subsequent maneuvers, and surfing performance overall. Despite this, no study has investigated coaching cues to determine their association with performance. This study investigated the frontside bottom turn, to identify critical features associated with quality performance, and second to determine whether any of these features could predict whether a surfer would subsequently perform either a cutback or a top turn maneuver. Videos of every frontside bottom turn from all finals heats of the 2017 World Surf League, Corona Open Jeffrey's Bay event were analyzed. A total of 199 frontside bottom turns were identified and categorized as either a bottom turn leading to a cutback maneuver (n = 106), or a bottom turn leading to a top turn maneuver (n = 93). A checklist of 47 potential critical features was developed after consultation with coaching and competition judging experts, thereby enabling a systematic analysis of each turn to determine the expected and actual frequency of occurrence for each potential feature. Consequently, an extensive list of critical features of the frontside bottom turn was identified and associated with a high level of performance, being executed successfully by professional athletes during high-stakes competition. Several features, particularly during the exit phase of the bottom turn, also helped predict whether these athletes subsequently performed either a cutback or a top turn maneuver. The findings of this study provide surf coaches with cues that can be used as a guide to effectively coach two main frontside bottom turn variations.